Le patrimoine, un argument de négociation pour l’aménagement d’un espace - Clément Colin (Territoire en Mouvement)
Regarding the consideration of the rivers as an heritage component, we are interesting in the places occupied and exploited by structures and equipments representing the engineer approach of the 20th century. What is the status given to these industrial sites and how the river reconquest actor's approach them ? Based on the hydro-electric production site of Cusset located in the northeast of Greater Lyon, this paper examines how the local actors use the argument of “heritage” in the frame of the renegotiation of the EDF concession (1991-2002). In the frame of the debates about the different uses of the river, we analyze the actor’s strategies and the role of the equipment’s managers and owners (dams, factory-dam, and diversion canal). From this case study, we question the heritage production in its instrumental and political dimensions.